Aqueous chlorination of mefenamic acid: Kinetics, transformation by-products and ecotoxicity assessment - Khalit, W.N.A.W.; Tay, K.S. (Royal Society of Chemistry, 2016)
Mefenamic acid (Mfe) is one of the most frequently detected nonsteroidal anti-inflammatory drugs in the environment. This study investigated the kinetics and the transformation by-products of Mfe during aqueous chlorination. The potential ecotoxicity of the transformation by-products was also evaluated. In the kinetic study, the second-order rate constant (kapp) for the reaction between Mfe and free available chlorine (FAC) was determined at 25 ± 0.1 °C. The result indicated that the degradation of Mfe by FAC is highly pH-dependent. When the pH was increased from 6 to 8, it was found that the kapp for the reaction between Mfe and FAC was decreased from 16.44 to 4.4 M-1 s-1. Characterization of the transformation by-products formed during the chlorination of Mfe was carried out using liquid chromatography-quadrupole time-of-flight accurate mass spectrometry. Four major transformation by-products were identified. These transformation by-products were mainly formed through hydroxylation, chlorination and oxidation reactions. Ecotoxicity assessment revealed that transformation by-products, particularly monohydroxylated Mfe which is more toxic than Mfe, can be formed during aqueous chlorination.